2022
DOI: 10.1007/s13555-022-00687-0
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Guide to the Management of Oral Candidiasis in Patients with Plaque Psoriasis Receiving Treatments That Target Interleukin-17

Abstract: Plaque psoriasis is an immune-mediated inflammatory skin disease associated with the dysregulation of cytokines, especially those involved in the interleukin (IL)-23/IL-17 pathways. In recent years, there has been growing interest in developing biologic therapies that target these pathways. However, inhibition of the cytokines of the IL-23/IL-17 pathways may increase patients' risk of developing fungal infections, particularly oral candidiasis. Therefore, it is important that dermatology practitioners can effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
5
2
0
1
Order By: Relevance
“…Most often, oral candidiasis was treated with nystatin and/or fluconazole and the majority of infections were reported to resolve with treatment (median duration of 12 days) [ 22 ]. This is consistent with prior literature on treatment of oral candidiasis resulting from anti-IL-17 therapy for psoriasis [ 47 49 ]. In general, treatments for oral candidiasis are effective and have low resistance rates [ 50 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Most often, oral candidiasis was treated with nystatin and/or fluconazole and the majority of infections were reported to resolve with treatment (median duration of 12 days) [ 22 ]. This is consistent with prior literature on treatment of oral candidiasis resulting from anti-IL-17 therapy for psoriasis [ 47 49 ]. In general, treatments for oral candidiasis are effective and have low resistance rates [ 50 ].…”
Section: Resultssupporting
confidence: 92%
“…Certain patient populations are at greater risk of developing candida infections. Predisposing risk factors include immunodeficiency (e.g., HIV, chemotherapy), antibiotics, older age, endocrine disorders, nutritional deficiencies, smoking, steroid inhalers, poor oral hygiene, and salivary hypofunction [ 49 ]. As such, candidal infections from bimekizumab can be effectively treated with current standard of care.…”
Section: Resultsmentioning
confidence: 99%
“…The dual inhibition of IL-17A and 17F by bimekizumab may contribute to its higher risk of infection. 40,41 This notion is also supported by previous reports that bimekizumab is associated with an increased incidence of oral candidiasis compared with other IL-17 inhibitors. 40,41 Several observational studies have analyzed the risk of serious infection related to targeted therapies in patients with psoriasis; however, these studies provided inconsistent results.…”
Section: Discussionsupporting
confidence: 74%
“…40,41 This notion is also supported by previous reports that bimekizumab is associated with an increased incidence of oral candidiasis compared with other IL-17 inhibitors. 40,41 Several observational studies have analyzed the risk of serious infection related to targeted therapies in patients with psoriasis; however, these studies provided inconsistent results. One large observational study conducted in the United States found that the risk of serious infection was slightly higher for biologic therapies compared with non-biologics (aHR, 1.31; 95% CI, 1.02-1.68).…”
Section: Discussionsupporting
confidence: 74%
“…Another possible explanation is that, as brodalumab inhibits IL-17 R, it prevents the activity of all other IL-17 cytokines, even IL-17E, which may indirectly inhibit Th17 responses (Iwakura et al 2011 ). In addition, if IL-17 R is not entirely prevented after the dosing cycle, residual IL-17 May likely confer defence against Candida (Armstrong et al 2022 ). However, further studies are required on this topic for better understanding.…”
Section: Comparison Of the Risk Of Candidiasis Between Different Il-1...mentioning
confidence: 99%